2021
DOI: 10.1002/tea.21734
|View full text |Cite
|
Sign up to set email alerts
|

Constructing STEM identity: An expanded structural model for STEM identity research

Abstract: Identity development frameworks provide insight into why and to what extent individuals engage in STEMrelated activities. While studies of "STEM identity" often build off previously validated disciplinary and/or science identity frameworks, quantitative analyses of constructs that specifically measure STEM identity and its antecedents are scarce, making it challenging for researchers or practitioners to apply a measurementbased perspective of participation in opportunities billed as "STEM." In this study, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 120 publications
0
46
0
Order By: Relevance
“…This relationship is mediated by interest and external recognition in mathematics, with recognition having a stronger direct effect. Dou and Cian (2022) recently confirmed the robustness of the Hazari et al (2010) framework in their structural equation model of the construct of STEM identity.…”
Section: Stem Learner Identitymentioning
confidence: 73%
See 1 more Smart Citation
“…This relationship is mediated by interest and external recognition in mathematics, with recognition having a stronger direct effect. Dou and Cian (2022) recently confirmed the robustness of the Hazari et al (2010) framework in their structural equation model of the construct of STEM identity.…”
Section: Stem Learner Identitymentioning
confidence: 73%
“…Carlone and Johnson (2007) have profoundly influenced how the field conceptualizes STEM learner identity. Researchers on STEM learner identity have operationalized these three dimensions in the pursuit of a generalizable model of STEM learner identity (Cribbs et al, 2015;Dou & Cian, 2022;Espinosa, 2011;Godwin, 2016;Hazari et al, 2010;McDonald et al, 2019;Paul et al, 2020). Hazari et al (2010), using data from the Persistence Research in Science and Engineering project, extended the Carlone and Johnson (2007) framework.…”
Section: Stem Learner Identitymentioning
confidence: 99%
“…According to the infectious disease theory, the SI model divides the population into two main types ( Figure 3 ): susceptible individuals (S) and infected individuals (I). During the spread of the disease, the infected individual will infect the surrounding susceptible population with a certain probability, and once the susceptible individual is infected with the virus, it will immediately become an infected individual and will never be cured [ 12 ].…”
Section: Emotional Mental Model Based On Crowd Evacuationmentioning
confidence: 99%
“…The single indicator represents students' overall perceptions of chemistry identity. Previous research in other fields (e.g., engineering) has demonstrated a positive relationship among the four aspects of identity, i.e., competence/performance beliefs influence students' overall perception of identity through the mediating role of interest and external recognition, respectively (Godwin et al, 2016;Dou and Cian, 2021; Verdı ´n, 2021) (as shown in Fig. 1).…”
Section: Methodsmentioning
confidence: 83%